Does the gender composition of forest and fishery management groups affect resource governance and conservation outcomes?: a systematic map - Leisher, C.; Temsah, G.; Booker, F.; Day, M.; Samberg, L.; Prosnitz, D.; Agarwal, B.; Matthews, E.; Roe, D.; Russell, D.; Sunderland, Terry C.H.; Wilkie, D. (Springer, 2016)
Women often use natural resources differently than men yet frequently have minimal influence on how local resources are managed. An emerging hypothesis is that empowering more women in local resource decision-making may lead to better resource governance and conservation. Here we focus on the forestry and fisheries sectors to answer the question: What is the evidence that the gender composition of forest and fisheries management groups affects resource governance and conservation outcomes? We present a systematic map detailing the geographic and thematic extent of the evidence base and assessing the quality of the evidence, as per a published a priori protocol.We screened 11,000+ English-language records in Scopus, CAB abstracts, AGRIS, AGRICOLA, Google Scholar, and Google. The websites of 24 international conservation and development organisations, references of included articles, and relevant systematic reviews were also searched for possible documents. A number of groups and individuals were invited to submit documents through email ‘call outs’. The inclusion criteria were that an article refers to women or gender, forests or fisheries, and a resource management group comparison in a non-OECD country plus Mexico and Chile.Seventeen studies met the inclusion criteria. Four were qualitative and 13 were quantitative. Forest studies outnumbered fisheries studies 14–3. The majority of the studies came from India and Nepal and focused on forest management. All 17 studies identified improvements in local natural resource governance, and three identified conservation improvements when women participated in the management of the resources. Only two studies, however, were rated as high quality based on study design.For India and Nepal, there is strong and clear evidence of the importance of including women in forest management groups for better resource governance and conservation outcomes. Outside of India and Nepal, there are substantial gaps in the evidence base, but the South Asian evidence presents a compelling case for extending the research to other geographies to see if similar outcomes exist elsewhere and supports a theory of change linking the participation of women in forestry and fisheries management groups with better resource governance and conservation outcomes.